The safety of the early removal of prophylactic drainage after liver resection based solely on predetermined criteria: a propensity score analysis. Issue 4 (April 2017) - Hokuto, Daisuke; Nomi, Takeo; Yasuda, Satoshi; Kawaguchi, Chihiro; Yoshikawa, Takahiro; Ishioka, Kohei; Obara, Shinsaku; Yamada, Takatsugu; Kanehiro, Hiromichi
Abstract: Background: Prophylactic drainage after liver resection remains a common practice amongst hepatic surgeons. However, there is little information about the optimal timing of drain removal. Methods: From April 2008 to December 2012 (conventional group), the drains were removed based on the treating surgeon's view. From January 2013 to April 2016 (ERP group), the drains were removed on POD 3 if the bile concentration of the drain discharge was less than three times the serum bilirubin on POD 3, and the amount of drain discharge was <500 ml on POD 3. The postoperative outcomes of the two groups were compared using one-to-one propensity score-matching analysis. Results: One hundred nine patients were extracted from ERP group (n = 226) and conventional group (n = 246). The time to drain removal was significantly shorter in the ERP group than in the conventional group (3 days vs. 5 days, P < 0.001). The frequency of delayed bile leakage or the appearance of symptomatic abdominal fluid collection after drain removal did not differ between the two groups (3% vs. 4%, P = 0.791). Conclusion: Drain removal on POD 3 based on the volume and bile concentration is safe.